American Telemedicine Association’s Principles for Delivering Telerehabilitation Services - Tammy Richmond; Christopher Peterson; Jana Cason; Mike Billings; Evelyn Abrahante Terrell; Alan Chong W. Lee; Michael Towey; Bambang Parmanto; Andi Saptano; Ellen R. Cohn; David Brennan (International Journal of Telerehabilitation)
Telehealth is a broad term used to describe the use of electronic or digital information and communications technologies to support clinical healthcare, patient and professional health related education, and public health and health administration. Telerehabilitation refers to the delivery of rehabilitation and habilitation services via information and communication technologies (ICT), also commonly referred to as” telehealth” technologies. Telerehabilitation services can include evaluation, assessment, monitoring, prevention, intervention, supervision, education, consultation, and coaching. Telerehabilitation services can be deployed across all patient populations and multiple healthcare settings including clinics, homes, schools, or community-based worksites. This document was adapted from the American Telemedicine Association’s (ATA) “A Blueprint for Telerehabilitation Guidelines” (2010) and reflects the current utilization of telerehabilitation services. It was developed collaboratively by members of the ATA Telerehabilitation Special Interest Group, with input and guidance from other practitioners in the field, strategic stakeholders, and ATA staff. Its purpose is to inform and assist practitioners in providing effective and secure services that are based on client needs, current empirical evidence, and available technologies. Rehabilitation professionals, in conjunction with professional associations and other organizations are encouraged to use this document as a resource for developing discipline-specific standards, guidelines, and practice requirements. Keywords: American Telemedicine Association, Habilitation, Rehabilitation, Telehealth, Telepractice